Breakdown in the brain network subserving moral judgment in criminal psychopathy - Pujol, Jesus (Oxford University Press, 2012)
Neuroimaging research has demonstrated the involvement of a well-defined brain network in the mediation of moral judgment in normal population, and has suggested the inappropriate network use in criminal psychopathy. We used functional magnetic resonance imaging (fMRI) to prove that alterations in the brain network subserving moral judgment in criminal psychopaths are not limited to the inadequate network use during moral judgment, but that a primary network breakdown would exist with dysfunctional alterations outside moral dilemma situations. A total of 22 criminal psychopathic men and 22 control subjects were assessed and fMRI maps were generated to identify (i) brain response to moral dilemmas, (ii) task-induced deactivation of the network during a conventional cognitive task and (iii) the strength of functional connectivity within the network during resting-state. The obtained functional brain maps indeed confirmed that the network subserving moral judgment is underactive in psychopathic individuals during moral dilemma situations, but the data also provided evidence of a baseline network alteration outside moral contexts with a functional disconnection between emotional and cognitive elements that jointly construct moral judgment. The finding may have significant social implications if considering psychopathic behavior to be a result of a primary breakdown in basic brain systems.